Feroz ul lughat: urdu jadeed(newedition) (Feroz sons Lahore, 2012)
"Feroz ul Lughat Jadeed" is a renowned Urdu dictionary that provides an extensive collection of words, meanings, and usage examples. The new edition updates entries and includes modern terminology, making it a valuable resource for students, writers, and language enthusiasts. Its user-friendly layout and comprehensive definitions help users enhance their vocabulary and understanding of the Urdu language, catering to both beginners and advanced speakers. This edition emphasizes clarity and accessibility, solidifying its place as an essential reference in Urdu literature and education.